Oral nutrition supplements and between-meal snacks for nutrition therapy in patients with COPD identified as at nutritional risk: a randomised feasibility trial - Arora Ros Ingadottir; Anne Marie Beck; Christine Baldwin; Christine Elizabeth Weekes; Olof Gudny Geirsdottir; Alfons Ramel; Thorarinn Gislason; Ingibjorg Gunnarsdottir (BMJ Open Respiratory Research)
Introduction Intervention studies have mainly used oral nutritional supplements (ONS) for the management of patients with chronic obstructive pulmonary disease (COPD) identified as at nutritional risk. In this 12-month randomised feasibility trial, we assessed the (1) feasibility of the recruitment, retention and provision of two interventions: ONS and between-meal snacks (snacks) and (2) the potential impact of the provision of snacks and ONS on body weight and quality of life in patients with COPD.Methods  Hospitalised patients with COPD, at nutritional risk, were randomised to ONS (n=19) or snacks (n=15) providing 600 kcal and 22 g protein a day in addition to regular daily diet. The intervention started in hospital and was continued for 12 months after discharge from the hospital.Results  Study recruitment rate was n=34 (45%) and retention rate at 12 months was similar for both groups: n=13 (68%) in the ONS group and n=10 (67%) in the Snacks group. Both groups gained weight from baseline to 12 months (2.3±4.6 kg (p=0.060) in the ONS group and 4.4±6.4 kg (p=0.030) in the Snacks group). The St George’s Respiratory Questionnaire total score improved from baseline to 12 months in both groups (score 3.9±11.0 (p=0.176) in the ONS group and score 8.9±14.1 (p=0.041) in the Snacks group).Discussion  In patients with COPD who are at nutritional risk snacks are at least as feasible and effective as ONS, however, adequately powered trials that take account of the difficulties in recruiting this patient group are required to confirm this effect.